Impaired Cognition and Brain Atrophy Decades After Hypertensive Pregnancy Disorders. (February 2016) - Mielke, Michelle M.; Milic, Natasa M.; Weissgerber, Tracey L.; White, Wendy M.; Kantarci, Kejal; Mosley, Thomas H.; Windham, B. Gwen; Simpson, Brittany N.; Turner, Stephen T.; Garovic, Vesna D.
Abstract : Background—: Hypertensive pregnancy disorders have been associated with subjective cognitive complaints or brain white-matter lesions 5 to 10 years after the hypertensive pregnancy. The long-term effects of hypertensive pregnancies on brain structure and cognitive function remain unknown. Methods and Results—: This study included 1279 women who participated in the Family Blood Pressure Project Genetic Epidemiology Network of Arteriopathy (GENOA) study. As part of the ancillary Genetics of Microangiopathic Brain Injury (GMBI) study, a neurocognitive battery was administered; 1075 also had a brain magnetic resonance imaging. A history of a hypertensive pregnancy disorder was obtained by a self-report using a validated questionnaire. Linear models fit with generalized estimating equations were used to assess the association between hypertensive pregnancy disorders and cognition, adjusting for age, race, education, body mass index, smoking, current hypertension, hypertension duration, and family history of hypertension. Regression models for the brain magnetic resonance imaging outcomes also were adjusted for total intracranial volume. Women with histories of hypertensive pregnancy disorders performed worse on all measures of processing speed (Digital Symbol Substitution Test [mean score, 41.2 versus 43.4; P =0.005], Trail Making Test Part A [mean seconds, 45.1 versus 42.2; P =0.035], and Stroop [mean score, 173.9 versus 181.0; P =0.002]) and had smaller brain volumes compared with women with histories of normotensive pregnancies (286 versus 297; P =0.023). Conclusions—: Hypertensive pregnancy disorders are associated with worse performance on tests of processing speed and smaller brain volumes decades later. Population-based studies are needed to provide critical insight as to the contribution of hypertensive pregnancies to risk of cognitive decline and dementia.